Antiplasmodial Effect of Anthocleista vogelii on Albino Mice Experimentally Infected with Plasmodium berghei berghei (NK 65). (11th May 2014) - Gboeloh, Lebari Barine; Okon, Okpok Eta; Udoh, Samuel Effiong
Abstract : The objective of the present study was to investigate the antiplasmodial effect of the ethanolic stem bark extract of Anthocleista vogelii at different doses in albino mice infected with Plasmodium berghei berghei (NK 65). Thirty-six mice were divided into six groups of six mice each. Five groups (B1 –B3, D, and G) were infected with Plasmodium berghei berghei parasitized red blood cells. Groups D, H, and G served as the controls. Six days after infection, mice in groups B1, B2, and B3 were treated orally with 100, 200, and 400 mg/kg body weight of Anthocleista vogelii, respectively, for six executive days. Group D was treated with 5 mg/kg body weight of chloroquine while Group G was given distilled water. Group H was not infected and was not treated. It served as the normal control. The extracts exhibited significant( P < 0.05 ) dose-dependent chemosuppression of P. berghei . The extract exhibited average chemosuppressive effects of 48.5%, 78.5%, and 86.6% at dose levels of 100, 200, and 400 mg/kg body weight, respectively. Phytochemical screening of the plant extract revealed the presence of saponins, cardiac glycosides, flavonoids, terpenes, alkaloids, and steroid. The acute toxicity (LD50 ) of the plant was estimated to be 3162 mg/kg body weight. It showed that the stem bark of A. vogelii possesses antiplasmodial property.